Changes in soil phosphorus fractions caused by cropping without nutrient reposition : a case study - Barresi, O. (2018)
Fil: Barresi, O. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Biología Aplicada y Alimentos. Cátedra de Microbiología Agrícola. Buenos Aires, Argentina.